Fate and Uptake of Pharmaceuticals in Soil–Earthworm Systems - Carter, Laura J. (American Chemical Society, 2014)
[Image: see text] Pharmaceuticals present a potential threat to soil organisms, yet our understanding of their fate and uptake in soil systems is limited. This study therefore investigated the fate and uptake of (14)C-labeled carbamazepine, diclofenac, fluoxetine, and orlistat in soil–earthworm systems. Sorption coefficients increased in the order of carbamazepine < diclofenac < fluoxetine < orlistat. Dissipation of (14)C varied by compound, and for orlistat, there was evidence of formation of nonextractable residues. Uptake of (14)C was seen for all compounds. Depuration studies showed complete elimination of (14)C for carbamazepine and fluoxetine treatments and partial elimination for orlistat and diclofenac, with greater than 30% of the (14)C remaining in the tissue at the end of the experiment. Pore-water-based bioconcentration factors (BCFs), based on uptake and elimination of (14)C, increased in the order carbamazepine < diclofenac < fluoxetine and orlistat. Liquid chromatography–tandem mass spectrometry and liquid chromatography–Fourier transform mass spectrometry indicated that the observed uptake in the fluoxetine and carbamazepine treatments was due to the parent compounds but that diclofenac was degraded in the test system so uptake was due to unidentifiable transformation products. Comparison of our data with outputs of quantitative structure−activity relationships for estimating BCFs in worms showed that these models tend to overestimate pharmaceutical BCFs so new models are needed.